Peningkatan Pembelajaran Microteaching Melalui Pendekatan Kolaboratif - Titin Untari; Rima Rahmaniah; Arpan Bilal Islami; Baiq Yuliatin Ihsani (Universitas Muria Kudus, 2018)
In designing lecture materials for one semester in the form of a concept map, there are some steps that are absolutely necessary, especially for lecturers for learning planning and microteaching. In accordance with the description, the purpose of this research is to describe the process of learning improvement with a collaborative approach. The method used in this study is a qualitative descriptive method with a descriptive approach and action. The subjects of the research were the 5th semester students of the Indonesian Language and Literature Education Study Program totaling 26 people, then the method of data collection using observation, tests and documentation. Data analysis uses a qualitative descriptive model with data reduction activities, data presentation, and data verification or draw conclusions. The results of this study indicate that learning through a collaborative approach can improve teaching skills and prepare teaching preparation. This is marked by several things, namely 1) the learning tools prepared by students in the form of concept maps to be discussed; 2) an increase in students 'ability or understanding is influenced by the availability of maximum learning tools, learning media that can hone students' mindset such as observing, identifying, analyzing, discovering new things, communicating, and concluding the concepts of skill set and teaching skills with refers to concept maps that are made and assisted with learning tools, namely RPS, RPM, methods, learning media, learning resources, assessment, then makes chapter designs and lesson designs that have been prepared by the lecturer.